THE CONTRIBUTION OF WATER RESOURCES TO SUSTAINABLE LOCAL DEVELOPMENT: INSIGHTS FROM TLEMCEN - Abdelhak, Benameur; Asma Hadjira, Sebbane; Abdel-illah, Khelassi (The journal of contemporary issues in business and government, 2024)
The article discusses the importance of water for human and environmental well-being, as well as the challenges and opportunities of water management in the context of sustainable development. The article focuses on the case of Tlemcen, a region in Algeria that has rich and diverse water resources, and how local authorities have implemented various projects to improve water services, reduce environmental impact, and enhance agricultural production. The article concludes by recommending further investment in water infrastructure and practices to ensure the long-term security and benefits of water for the region and the world.